The blood of Olympus - Riordan, Rick. (Los Angeles ; New York : Disney-Hyperion Books, 2014)
"The Greek and Roman demigods must simultaneously prevent the earth mother, Gaea, from waking and stop war from breaking out at Camp Half-Blood"--
Keywords: Mythology, Greek -- Juvenile fiction; Mythology, Roman -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction